Disappearance of Philosophy of Education: Paradox or Norm? - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2005)
The article deals with the analysis of philosophy of education in Lithuania. The fact of weakness of the philosophy of education is explained from two perspectives. The first one analyses a new situation of philosophy in general and changes of philosophy of education in the world, when researchers try to define the relationship between philosophy and education in a present day situation. And the other perspective describes a rather closed situation in the educational science in contemporary Lithuania, when philosophy as a methodology becomes an unrecognizable „educational" methodology. The danger of such situation is exposed in comparison with the postmodern theory about the power of educational discourse and control (Foucault). Finally some suggestions of how to change this situation in Lithuania are formulated.
Keywords: philosophy of education; contemporary philosophy; education science; Lithuania